The comparison of nutritional and physical activity statuses in students of Audiology and Nutrition & Dietetics - Ayşe Güneş Bayir; Zeynep Hüdanur Alban (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2020)
This study aimed to assessment and compare nutritional and physical activity status of Nutrition&Dietetics and Audiology Departments. The study was carried on students of Bezmialem Foundation University Faculty of Health Sciences Nutrition&Dietetics (experimental group) and Audiology (control group) Departments in 2016/2017 academic year. The survey included socio-demographic characteristics, 24-h recall Food Consumption Record, Food Frequency Questionnaire to determine nutrition and physical activity. Body Mass Index, waist circumference and body fat mass ratios were measured by bioelectrical impedance device. Overall, 220(66%) students participated, 125(84%) from experimental group and 95(46%) from control group. 75% of experimental group and 73% of control group were calculated as normal weight and mean body fat ratios were normal (24.3% and 22.8%, respectively). However, energy, water, carbohydrates, some vitamins and minerals were inadequate for two groups and fat consumption levels were high. 34% of those in control group had skipped breakfast meals, and they had unhealthy attitudes like chocolate and biscuits. Daily dairy products consume were found experimental group more than control group (p<0.05). 55% of experimental group and 58% of control group had regular physical activity.  Health professionals need to be more conscious about healthy life, which includes adequate-balanced nutrition and regular physical activity.